Graphene reinforced hybrid-bioceramic coatings on porous-Ti6Al4V for biomedical applications: morphology, corrosion resistance, and cell viability - Aslan, N.; Aksakal, B.; Dikici, B.; Sinirlioglu, Z. A. (SPRINGER, 2022)
The effect of Hydroxyapatite (HA)-based coatings reinforced with reduced graphene oxide (rGO) on porous-Ti6Al4V (P-Ti6Al4V) alloys in terms of electrochemical corrosion and cell viability for potential biomedical applications was investigated in this study. The scaffold-porous surfaces of P-Ti6Al4V were coated by the biocomposite structure of HA and reduced graphene oxide (rGO) at various porosity rates (40, 50, and 60%) by using the sol-gel dip-coating method. The results of 0.5, 1.0, and 1.5 wt% rGO-HA coatings were compared to coatings that contained only HA (free-rGO). Raman spectroscopy, X-ray diffractometer, and scanning electron microscopy were used for structural and morphological characterizations. The coatings in vitro corrosion susceptibilities were tested in simulated body fluid at 37 degrees C. Compared to free-rGO coatings, the results showed that rGO reinforcements phases reduced the corrosion rate of the scaffolds. The corrosion rate increased as the porosity content of the scaffolds increased. In vitro cell viability tests revealed that samples of 0.5 and 1.0 wt% rGO-HA coating groups performed better than the control and 1.5 wt% rGO-HA samples.
Keywords: TITANIUM-ALLOYS; HYDROXYAPATITE; OXIDE; DEPOSITION; IMPLANTS; SCAFFOLDS; Materials Science